The Influence of Self-Efficacy and Locus of Control on Student Achievement in Economics Subject - Ismail; Licence; Yulistiana; Nazaruddin Ali Basyah (Universitas Pendidikan Ganesha, 2023)
There were still many students who had low self-efficacy and locus of control. Students feel insecure so they tend to depend on students who are smarter. This study aims to analyze the effect of self-efficacy and locus of control on student achievement in twelve grade accounting class at senior high school. This research uses a quantitative approach with descriptive methods. The sampling technique in this study is simple random sampling. The data analysis technique used is multiple linear regression analysis by testing the hypothesis using the t test and f test. The results of the study show that: (1) There is a positive and significant influence between self-efficacy and student achievement as evidenced by the t-count 3,633 > t-table 2,00575 at the 5% significance level.; (2) There is a positive and significant influence between locus of control with student achievement indicated by t-count 6,037 > 2,00575 at the 5% significance level.; (3) There is a positive and significant influence between self-efficacy, locus of control together with student achievement indicated by R Square 0.828 and f count of 139.923 > f table with (df: 2; 53) a significant level of 5% which is equal to 3.17. Based on the results of the analysis it can be concluded that the variables of self-efficacy and locus of control both affect learning achievement, where students who have self-efficacy and locus of control which is good then it will be able to improve learning achievement.